Effect of Adding Carrot Flour (Daucus sp) and Yellow Pumpkin Flour (Cucurbita sp) on Artificial Feed on Color Quality Platy Sword Fish (Xyphophorus helleri) - Suci Rama Putri; Rusliadi Rusliadi; Mulyadi Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT Color is one reason of ornamental that are demand by the community so that farmers need to maintain the color of ornamental fish by feeding which contains color pigments. The effort taken to get a bright color that is evenly distributed to fish is to add a source of pigment to the feed. The ornamental fish business is not enough to rely only on efforts to spur the production of ornamental fish, but it needs to be accompanied by efficient steps regarding the appearance of color beauty, for this reason we need feed added with carrot flour and pumpkin to improve the quality of the color.The method that will be used in this study is an experimental method using a completely randomized design (CRD) of one factor which consists of 4 levels of treatment with three replications so that it takes 12 experimental units. Each treatment is: P0 = 100% pellet, Pı = Pellet 95% + 5% carrot flour, P2 = Pellet 95% + 5% pumpkin flour, Pɜ = Pellet 95% + 2.5% carrot flour + Pumpkin flour yellow 2.5%. Parameters observed included changes in color quality, absolute weight growth, absolute long-term growth, survival rate and water quality (pH, temperature, DO and Ammonia.The results showed that the best treatment for color quality improvement was takari + carrot pellets 2.5% + pumpkin 2.5%, while takari pellet + 5% pumpkin is best for increasing absolute weight growth (0.273 grams), absolute length growth (0.530 cm) and 100% survival rate. Feeding from takari pellets + 2.5% carrot flour + pumpkin 2.5 % can be applied to efforts to improve the quality of color for ornamental fish farmers,Water quality parameters during the study such as water temperature ranging from 27.2-28.5 oC, acidity (pH) water 6.7-7.6, dissolved oxygen content (DO) between 5.1- 7,4mg / L and ammonia between 0,000 - 0,046mg / L. Values of water quality parameters during the study still supports for the life and growth of platy fish fry sword.Keywords: Staining; Artificial Feed; Carrot; Summer squash; Platy Sword (Xyphophorus helleri)